CHARACTERISTICS OF MINDFULNESS BASED INTERVENTIONS FOR DIFFERENT PATIENT GROUPS – LITERATURE REVIEW - Majore-Dūšele, Indra; Paiča, Inese; Mārtinsone, Kristīne; Millere, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Mindfulness based interventions has been used in context with different mental and somatic health conditions in health care system with good evidences. In Latvia professionals working in psychiatry and rehabilitation are taking first steps to integrate mindfulness based interventions into their practice, therefore, guidelines for integration these interventions into the health care system is needed. The aim of this study is to evaluate existing evidences, content and mechanisms of mindfulness interventions for different patient groups.Electronic searches in PubMed, ProQuest, ScienceDirect, ClinicalKey, Cochrane Library, Wiley Online Library, and PsycInfo (2010 – 2018). Papers were required to meet the following criteria to be included in this review: (i) systematic review or meta-analysis; (ii) include quantitative outcomes for adult population in health care setting; (iii) published in English.Despite the good evidences, mindfulness based interventions are viewed as "complex intervention", researchers call for methodological, cultural and ethical attention to be made of implementing mindfulness practice into health care setting.